Characterization of Sulfonated, Radiation-Induced Polystyrene-Grafted Fluorinated Base Polymer Proton Exchange Membranes - Hussain, Muhammad Yousuf (2007)
The world’s future is critically energy dependent and the concerns of the global warming caused by the present-day depleting non-renewable fossil fuels push the development of new technologies for clean, efficient, reliable, and portable power sources based on electrochemical devices such as fuel cells. The hydrophilic proton exchange membranes (PEMs) seem to be a vital component of fuel cells. Currently, the commercial perfluoro-sulfonated PEMs are inheritably very expensive and an alternative PEM must be sought after, which possess properties suitable for fuel cell applications. Rationalizing this circumstance, sulfonated membranes have been developed by graft copolymerization of styrene onto PTFE, ETFE and PVDF base polymer films using a simultaneous gamma irradiation method and their physico-chemical properties were investigated. Factors affecting the grafting yield, namely the radiation dose, styrene concentration and type of solvent have been identified. Dichloromethane solvent was found to enhance the grafting yield considerably without the formation of homopolymer, unlike methanol and toluene tested, and therefore, dichloromethane was used in the subsequent grafting of styrene (20-100% v/v) onto the base films. The PTFE-g-polystyrene, ETFE-g-polystyrene, and PVDF-g-polystyrene films of different grafting yields were sulfonated using chlorosulfonic acid (30% v/v) diluted in dichloroethane (70% v/v) at the reactor temperature of 90 oC for 4 h in order to permit sulfonic acid functional group, SO3H attachment to the phenyl group of grafted polystyrene and consequently alternative PEMs were materialized. The grafting and sulfonation yields have been interpreted in terms of conventional two-compartmental analysis that gives the degrees of grafting (DOG) and sulfonation (DOS) and in terms of new three-compartmental analysis, which assumed the membrane consists of base polymer, polystyrene, and sulfonic acid, to yield the polystyrene content (PC) and the sulfonic acid content (SC). It was found that the DOG increases with radiation dose until the maximum DOG value of 73% for ETFE-g-polystyrene, 33% for PVDF-g-polystyrene, and 30% for PTFE-g-polystyrene at 25 kGy attributed to the initiation and propagation of graft copolymerization. Upon sulfonation, it was found that the DOS increases in proportionality to the DOG for all the sulfonated membranes. The results also revealed the dependences of the SC on PC and the DOS on DOG. Moreover, the mass ratio of the SC to the sulfonated polystyrene (PC+SC) is found in the range 55-59 % for higher grafting yield of sulfonated ETFE membranes and 51-54% for low grafting yield of sulfonated PTFE and PVDF membranes independent of the PC and SC obtained. Our DOS or SC results seem to differ to some previous results which openly declared the DOS values of 100% that is in contradicting to the physical nature of sulfonation mechanism. The physico-chemical i.e. ion exchange capacity (IEC) and activation energy behaviours of the sulfonated membranes were studied as functions of DOG (PS) and DOS (SC). The IEC is proportional to the DOS or SC. The IEC values vary between 0.721 and 1.095 mmol/g at DOS between 10.0 and 18.8% (SC between 9.0 and 17.6%) for the sulfonated PTFE- membranes, between 1.361 and 1.997 mmol/g at DOS between 26.8 and 55.3% (SC between 21.1 and 35.5%) for the sulfonated ETFE membranes, and between 0.360 and 0.432 m mol/g at DOS between 12.4 and 17.1% (SC between 11.1 and 14.6%) for the sulfonated PVDF membranes. The activation energies on the other hand vary between 0.327 and 0.275 eV at DOG between 10.4 and 22.0% (PC between 8.6 and 14.9%) for the sulfonated PTFE- membranes, between 0.227 and 0.170 eV at DOG between 25.4 and 60.9% (PC between 16.0 and 24.4%) for the sulfonated ETFE membranes, and between 0.3297 and 0.289 eV at DOG between 12.6 and 17.0% (PC between 9.9 and 12.4%) for sulfonated PVDF membranes. The effects of DOG (or PS) and DOG (or SC) on the thermal properties and chemical stability were also investigated. The glass transition temperature of the grafted membranes was found to show at a value of ~115 oC. The sulfonated membranes showed a chemical stability up to a temperature of ~300 oC above to which they undergo a multi step degradation pattern due to dehydration, desulfonation, decomposition of the polystyrene and sulfonic acid in the polymer matrices. For the purpose of morphological investigations, SEM micrographs of the grafted films and sulfonated membranes were taken while the SEM micrographs of their original and grafted samples were used as references respectively. This study revealed that for the low grafting yield the grafting concentrated at the surface of the graft copolymer and when the yield increases, the styrene monomer penetrated to the bulk and for the highest grafting yield achieved, the micrographs show the grafting presence until in the middle of the base films.